TRANSFORMATION OF THE STUDENTS’ INQUIRY CAPABILITY THROUGH MINDMAP EDUCATIVE BY USING GAME OBSERVATION NORMATIVELY (MEGONO) LEARNING MODEL - Tasiwan, T. (Jurnal Pendidikan IPA Indonesia, 2016)
This classroom action research was conducted to analyze the development of the students’ inquiry abilities in science learning by a learning model of mindmap educative by using game observation normatively (Megono). The study was conducted in three cycles. In each cycle, the students were divided into five groups, each groups consisted of seven students. Each group was mandated to observe and to analyze the images/photos. After the image observations, they were asked to discuss, write and compile the information into a concept map.  One of the students was act as a representative of the group in a game of observation. Data were obtained through the pre-test, post-test, and observation by the observers as well as from the photo and video recording. The results showed that the students’ inquiry ability increased by 63.27% at the end of the cycle. At the initial conditions, the ability of the student was low (0.49). After the first cycle, it increased to 0.63 (medium), and then increased to 0.68 (moderate) on the second cycle, and finally it increased to 0.80 (high) in the third cycle. The average increase in every aspect was 68.59%.  The highest inquiry capability was achieved in aspects of reasoning amounted to 89.29 (very high). It was suggested to use the observation games fairly and needed more time adjustment to obtain higher learning outcomes.